CONCEPTUAL APPROACH FOR METHODS AND TECHNIQUES UNDERLYING THE DECISION – EFFECTIVE MANAGEMENT TOOLS - Popovici V.E. Virgil - Ion (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
In today's society, one of the social subsystems, education, involves educational influences not easy to predict and to assess. The adapting problems of schools to the requirements of a good developmen are because, education integrates pedagogical, scientific, cultural progress and increasingly those in psycho-pedagogy concerning the balance between the scope and content of the objectives, assessment methods etc.Un important role in managerial success in higher education institutions is the university's strategy on how to develop on short, medium and long term. The decision may be synthesized from the set of definitions as an option and will act for a certain course of action, several alternatives / strategies available, aiming at achieving a certain goal based on an evaluation process, on the means necessary and the consequences of its realization that generates a particular change in the behavior of those involved.